Eskimo woman, Alaska, 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Eskimo Underwear made of Reindeer-skin. Nowell, 1904. 1024 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number